Upside-Down Down-Under: Cold Temperatures Reduce Learning in Australia - David W. Johnston; Rachel Knott; Silvia Mendolia; Peter Siminski (Institute of Labor Economics (IZA), 2021)
Understanding how variation in weather and climate conditions impact productivity, performance and learning is of crucial economic importance. Recently, studies have established that high temperatures negatively impact cognition and educational outcomes in several countries around the world. We add to this literature by analysing test scores from a national assessment of Australian children aged between 8 and 15 years. Using comparable methods to previous studies, we find that high temperatures in the year prior to the test do not worsen performance. In fact, we find the opposite: additional cold days significantly reduces test scores. Moreover, the effect appears cumulative, with cold school days 1-2 years prior also having a negative effect. This seemingly contradictory finding is consistent with a literature which finds that people living in warm regions tend to inadequately protect themselves from cold temperatures, meaning they are susceptible to cold weather shocks. More generally, we demonstrate that effects of weather conditions are likely to be context specific.
Keywords: I20; J24; J54; 330; learning; climate; Australia